Up-regulation of MiR-146b-5p Inhibits Fibrotic Lung Pericytes via Inactivation of the Notch1/PDGFRβ/ROCK1 Pathway - Shuai, W; Chen, Q; Zhou, X (Folia biologica, 2022)
Lung fibrosis is a serious human pathology. MiR-146b-5p is down-regulated in idiopathic pulmonary fibrosis, and the Notch1/PDGFRβ/ROCK1 pathway is activated. However, the relation between miR-146b-5p and the Notch1/PDGFRβ/ROCK1 pathway in lung fibrosis remains unclear. To investigate the function of miR-146b-5p in lung fibrosis, an in vivo model of lung fibrosis was established in mice by bleomycin. The fibrosis in lung tissues of mice was observed by HE, Masson and Sirius Red staining. Lung pericytes were isolated and identified by fluorescence microscopy. Immunofluorescence staining and Western blot were used to investigate the expression of desmin, NG2, collagen I and α-SMA. CCK8 assay was used to assess the cell viability, and flow cytometry was performed to evaluate the cell cycle in pericytes. Furthermore, the correlation between miR-146b-5p and Notch1 was analysed by Spearman analysis. The mechanism by which miR-146b-5p affects pericytes and lung fibrosis via the Notch1/ PDGFRβ/ROCK1 pathway was explored by RT-qPCR, Western blot, immunofluorescence staining and dual luciferase reporter gene assay. In bleomycin-treated mice, miR-146b-5p was down-regulated, while Notch1 was up-regulated. Up-regulation of miR-146b-5p significantly inhibited the viability and induced G1 phase arrest of lung pericytes. MiR-146b-5p mimics up-regulated miR-146b-5p, desmin, and NG2 and down-regulated α-SMA and collagen I in the lung pericytes. Additionally, miR-146b-5p was negatively correlated with Notch1, and miR-146b-5p interacted with Notch1. Over-expression of miR-146b-5p inactivated the Notch1/PDGFRβ/ROCK1 pathway. Our results indicate that up-regulation of miR-146b-5p inhibits fibrosis in lung pericytes via modulation of the Notch1/PDGFRβ/ROCK1 pathway. Thus, our study might provide a novel target against lung fibrosis.
Keywords: MicroRNAs; Collagen; plicní fibróza; lidé; bleomycin; mikro RNA; upregulace; receptor Notch1; desmin; myši; Humans; Pulmonary Fibrosis; pericyty; Mice; Receptor, Notch1; kolagen; zvířata; Desmin; Bleomycin; Animals; kinázy asociované s rho; Pericytes; Lung; Up-Regulation; plíce; rho-Associated Kinases